Professional and Character-Based Teachers: Embodying Exemplary Behavior and Humanitarian Values ​​through Digital Media - Miladiyah Ainun; Abdulloh Assa’diy (IJCRE - International Journal of Culture, Religion, and Education, 2025)
This study aims to analyze the practices of professional and character-based Islamic Religious Education (PAI) teachers at the UPT SD Negeri Ngeni 06 Wonotirto in shaping exemplary behavior and humanitarian values through digital media. The research employed observation, semi-structured interviews, and documentation to obtain comprehensive data on teacher learning practices and student responses. The collected data were then analyzed using a qualitative descriptive approach through the stages of data reduction, data display, and conclusion drawing.The results show that teachers act as active facilitators, utilizing digital presentations, learning videos, interactive quizzes, AI-based discussions, and digital e-portfolios to encourage student reflection, creativity, and critical thinking. Teacher role-modeling practices strengthen the internalization of character values. Digital media increases student motivation and participation, making character learning more effective. These findings emphasize the importance of digital innovation in shaping a superior generation with noble character.